Effect of Ar/CH4 Mixture Ratio on Properties of Ag/C:H Nanocomposite Prepared by DC Sputtering - E. Mohsen Soltani; Z. Ghorannevis; M. Shirazi (Advances in Materials Science and Engineering)
Ag/C:H films were deposited by DC sputtering method on Si substrates with different Ar/CH4 gas mixture ratios. Effect of Ar/CH4 gas mixture ratios was investigated on optical and structural properties of Ag/C:H films by FTIR spectroscopy analysis, X-Ray diffractometry (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM), respectively. In order to evaluate the effect of gas flow ratio on the optical and structural properties of Ag/C:H films, Ar/CH4 gas ratio was changed by keeping the Ar flow rate constant while varying the CH4 gas flow rate (2, 5, and 10 SCCM). From FTIR analysis it was observed that increase in the Ar/CH4 gas ratio results in decreasing the sputtered Ag nanoparticles and increasing of C–H bonds. Also from XRD pattern it was found that intensity of Ag crystalline plane and average grain size decrease by adding CH4 to working gas admixture. From SEM and AFM micrographs, size of the grains also became smaller on the surface of the films, which will lead to decreasing the roughness of the deposited thin films.